Residential exposure to traffic-borne pollution as a risk factor for acute cardiocerebrovascular events: a population-based retrospective cohort study in a highly urbanized area. (19th July 2021) - Magnoni, Pietro; Murtas, Rossella; Russo, Antonio Giampiero
Abstract: Background: Long-term exposure to traffic-borne noise and air pollution has been variably associated with incidence of acute vascular events, namely acute myocardial infarction, ischaemic stroke and haemorrhagic stroke. This study aims at exploring this association within a highly urbanized city. Methods: This is a population-based retrospective dynamic cohort study including all residents aged ≥ 35 years in the municipality of Milan over the years 2011–18 (1 087 110 inhabitants). Residential exposure to road traffic noise (day-evening-night levels) and nitrogen dioxide was estimated using a noise predictive model and a land use regression model, respectively. Cox proportional hazards regression analyses were performed to assess the incidence of acute vascular events and specific outcomes in single-exposure and two-exposure models including adjustment for sociodemographic confounders, fine particulate matter and surrounding greenness. Results: A total of 27 282 subjects (2.5%) had an acute vascular event. Models using nitrogen dioxide produced inconsistent results. The strongest effect was observed for noise, with an optimal cut-off for dichotomization set at 70 dBA (hazard ratio 1.025, 95% confidence interval 1.000–1.050). This association was observed specifically for ischaemic and haemorrhagic stroke. When stratifying by age group and sex, a remarkable effect was found for haemorrhagic stroke in men aged <60 years (hazard ratio 1.439, 95% confidence interval 1.156–1.792). Conclusions: Living by roads with a day-evening-night noise level above 70 dBA exerts a small but tangible independent effect on the risks of both ischaemic and haemorrhagic stroke. It is urgent to propose mitigation measures against pollution and noise originating from vehicular traffic in order to reduce their impact, especially in the population younger than 60 years.